Social Rehabilitation After Natural Disasters: Access and Adaptation of Education for Children Affected by Floods in Sumatra - Muhammad Bambang Purwanto; Ismail Nasar; Fitria Marisya; Anggra Prima; Jamilah Jamilah (Universitas Islam Sultan Agung, 2026)
Severe floods in the Sumatra region have had profound social and educational impacts, especially for school-age children who have lost access to the learning process due to infrastructure damage, family relocation, and psychological trauma. Education as a fundamental right of children needs to be guaranteed to continue even in emergency conditions. This study aims to analyze the conditions of access to education for children affected by floods, the form of adaptation of the learning system implemented in the affected areas, and the role of social rehabilitation in supporting the recovery of education and the welfare of children after the disaster. This study employs a descriptive, qualitative approach using a phenomenological method, focusing on the social and educational experiences of flood victims in Agam Regency, West Sumatra. Data were obtained through semi-structured interviews, participatory observations, and documentation studies of teachers, parents, social volunteers, and children of disaster victims. Data analysis was conducted using a thematic analysis approach, focusing on central themes such as access to education, learning adaptation, and social rehabilitation support. The results show that children's access to education remains limited due to damage to school facilities and the relocation of residents; however, local initiatives, such as emergency schools and child-friendly spaces, have emerged to protect the right to learn. Adaptation of empathy-based learning and social activities helps students recover emotionally. Social rehabilitation plays a vital role in rebuilding learning motivation, strengthening community collaboration, and creating a humanistic and inclusive emergency education system. This study emphasizes that integrating education, psychosocial, and social rehabilitation is key to sustainable post-disaster recovery and the development of resilience education in Indonesia.